Successful Brain Delivery of Andrographolide Loaded in Human Albumin Nanoparticles to TgCRND8 Mice, an Alzheimer’s Disease Mouse Model - Bilia, Anna Rita; Nardiello, Pamela; Piazzini, Vieri; Leri, Manuela; Bergonzi, Maria Camilla; Bucciantini, Monica; Casamenti, Fiorella (Frontiers in Pharmacology, 2019)
Andrographolide (AG) was encapsulated in human albumin nanoparticles (AG NPs) and their crossing properties of the blood brain barrier (BBB), brain distribution, and effects in TgCRND8 mice were evaluated. The development of appropriate NPs formulations is mandatory because of the scarce BBB permeability properties of AG. Developed NPs had proper size (mean size: 159.2±4.5 nm), size distribution (PDI nearby 0.12±0.01) and ζ-potential (-24.8±1.2 mV) which were not affected by sodium fluorescein (NAF) loading. When AG was loaded to NPs, it slightly affected their size (210.4±3.2 nm) and ζ-potential (-20.3±1.5), but not the PDI. Both NAF and AG had a remarkable encapsulation efficiency (more than 99%). The in vitro release of AG from the NPs reached the highest percentage (48%) after 24 h and the Higuchi's equation was found to be the best fitting model (R2=0.9635). Both AG and AG NPs did not alter the viability of N2a murine neuroblastoma cells when compared with the untreated control cells. In the step down inhibitory avoidance test, AG NPs administered to TgCRND8 mice significantly improved their performance (P<0.0001) reaching levels comparable to those displayed by wild type mice. In the object recognition test, treated and untreated animals showed no deficiencies in exploratory activity, directional movement towards the objects and locomotor activity. No cognitive impairments (discrimination score) were detected in TgCRND8 mice (P<0.0001) treated with AG NPs. After acutely i.v. administration (200µl) NPs loaded with the probe NAF were detected in the brain parenchyma of TgCRND8 mice. The immunofluorescent analyses evidenced the presence of NPs both in the pE3-Aβ plaque surroundings, and inside the pE3-Aβ plaque, indicative of the ability of these NPs to cross the BBB and to penetrate in both undamaged and damaged brain tissues. Furthermore, the immunohistochemical analysis of GFAP positive astrocytes in the hippocampus of Tg mice evidenced the anti-inflammatory activity of AG when AG NPs were ip administered. AG was not effective in counteract amyloid Aβ aggregation and the resulting toxicity, but significantly decreased the oxidative stress levels. In conclusion, AG NPs have extraordinary versatility, nontoxicity, non-immunogenicity, strong biocompatibility, highly biodegradability and astonishing loading capacity of drug.